An Overview of in vitro Methods to Study Microglia - Timmerman, Raissa; Burm, Saskia M.; Bajramovic, Jeffrey J. (Frontiers in Cellular Neuroscience, 2018)
Neuroinflammation is a common feature in neurodegenerative diseases and strategies to modulate neuroinflammatory processes are increasingly considered as therapeutic options. In such strategies, glia cells rather than neurons represent the cellular targets. Microglia, the resident macrophages of the central nervous system, are principal players in neuroinflammation and detailed cellular biological knowledge of this particular cell type is therefore of pivotal importance. The last decade has shed new light on the origin, characteristics and functions of microglia, underlining the need for specific in vitro methodology to study these cells in detail. In this review we provide a comprehensive overview of existing methodology such as cell lines, stem cell-derived microglia and primary dissociated cell cultures, as well as discuss recent developments. As there is no in vitro method available yet that recapitulates all hallmarks of adult homeostatic microglia, we also discuss the advantages and limitations of existing models across different species.